2013
DOI: 10.1002/ana.23721
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment and cortical degeneration in neuromyelitis optica

Abstract: We demonstrate cognitive impairment and substantial cortical neuronal loss with unique AQP4 dynamics in astrocytes in NMOsd. These data indicate pathological processes consisting not only of inflammatory demyelinating events characterized by pattern-specific loss of AQP4 immunoreactivity but also cortical neurodegeneration in NMOsd brains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

36
182
9
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 143 publications
(237 citation statements)
references
References 49 publications
36
182
9
10
Order By: Relevance
“…These impaired cognitive domains have frequently been reported in patients with NMO. 10,18,[21][22][23][24] However, inconsistent with previous studies that reported deficits in immediate memory, attention, and executive abilities, 10,17,18,21,23,24 we did not find any significant changes in these 3 cognitive domains in the patients with NMO. This discrepancy may be related to variations in the sample size, demographic and clinical features, and cognitive scales used.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…These impaired cognitive domains have frequently been reported in patients with NMO. 10,18,[21][22][23][24] However, inconsistent with previous studies that reported deficits in immediate memory, attention, and executive abilities, 10,17,18,21,23,24 we did not find any significant changes in these 3 cognitive domains in the patients with NMO. This discrepancy may be related to variations in the sample size, demographic and clinical features, and cognitive scales used.…”
Section: Discussioncontrasting
confidence: 99%
“…We found that the intergroup GMV differences were similar before and after excluding these patients (On-line Fig 3), suggesting that the impact of comorbidities on the intergroup GMV comparisons was not significant. Consistent with prior findings, 10,17,18,[21][22][23][24] we also found cognitive impairment in the patients with NMO. The cognitive impairments in NMO were deficits in short-and long-term memory, speed of information processing, and verbal fluency on semantic stimuli.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…7 Lesion probability maps have not found statistically significant lesion locations in patients positive for anti-AQP4 antibody over those with MS. 6 However, distinguishing features were identified on MS brain MRI that were sensitive and specific, such as the presence of a lateral ventricle and inferior temporal lobe lesion, Dawson fingers, or an S-shaped U-fiber lesion, to classify the patient as MS. Imaging sensitive to cortical lesions has revealed their absence in NMO (excluding one Japanese study of NMO pathology 48 ), whereas they are seen in the majority of patients with MS. 49,50 Characteristic MS brain lesions surround central venule in .80% on high-strength MRI. 50,51 In NMO lesions, this is less frequent, reported in 9% to 35% of cases 50,52 and likely indicates the different pathogenic mechanisms of the disease.…”
Section: Comparing the Imaging Of Nmosd Withmentioning
confidence: 99%